Cultural Landscape Tourism Development Model In Koto Gadang, West Sumatra - Ramadan, Rahmad; Emriadi, Haviz; Syafran, Syafran (Journal of Tourism Sciences, Technology and Industry, 2024)
Koto Gadang, a village located in Agam Regency, West Sumatra, holds extraordinary cultural and historical wealth. As one of the heritage tourism destinations in Indonesia, Koto Gadang has various attractions, such as the architecture of the traditional houses, silver crafts, and historical values of national figures who were born in this area. The research method in this study uses a qualitative descriptive method and data collection techniques using observation, documentation and literature studies. This study aims to identify the form of saujana as a potential heritage tourism in Koto Gadang such as the uniqueness of the Community, religious values, historical values in Koto Gadang and analyze the challenges faced, and offer sustainable development strategies to increase the appeal of tourism in this area. Keywords: heritage tourism, Koto Gadang, culture, history, tourism development